PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BINTANG NIAGA JAYA DICABANG HONDA BINTANG MOTOR CISEENG KABUPATEN BOGOR - Cesa Fireta Arisandy; Suwanto (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of work motivation and work discipline on employee performance at PT Bintang Niaga Jaya Branch of Honda Bintang Motor Ciseeng, Bogor Regency. The method used is a quantitative descriptive method. The sampling technique used is saturated sampling. The sampling method uses the Solvin formula. Data analysis uses the Classic Assumption Test, Simple Linear Regression Test, Multiple Linear Regression Test, Correlation Coefficient Test, Determination Coefficient Test, Hypothesis Testing. Based on the research results, it was found that work motivation does not have a significant influence on employee performance, with a t-count value of 1.223 < t-table of 2.009, and a significance value of 0.227 > 0.05. On the other hand, work discipline has a significant influence on employee performance, with a t-count of 5,187 > t-table 2,009, and a significance value of 0.000 < 0.05. Apart from that, the simultaneous test results show that work motivation and work discipline together have a significant effect on employee performance. This is supported by the F-count value of 26.216 > F-table of 3.19, with a significance value of 0.000. The results of the coefficient of determination test show that 51.7% of the variation in employee performance can be explained by work motivation and work discipline, while the remaining 48.3% is influenced by other factors.